2020
DOI: 10.3390/mi11050504
|View full text |Cite
|
Sign up to set email alerts
|

150–200 V Split-Gate Trench Power MOSFETs with Multiple Epitaxial Layers

Abstract: A rating voltage of 150 and 200 V split-gate trench (SGT) power metal-oxide- semiconductor field-effect transistor (Power MOSFET) with different epitaxial layers was proposed and studied. In order to reduce the specific on-resistance (Ron,sp) of a 150 and 200 V SGT power MOSFET, we used a multiple epitaxies (EPIs) structure to design it and compared other single-EPI and double-EPIs devices based on the same fabrication process. We found that the bottom epitaxial (EPI) layer of a double-EPIs structure can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…However, the counterpart of CSGT-MOS is located at the bottom trench. The peak electric field in the middle of the drift region is helpful to redistribute the electric field [12][13][14][15], and thus a more uniform electric field is formed in the HKP SGT-MOS and SSGT-MOS. It is clear that the electric field of HKP SGT-MOS decreases much more slowly than that of the SSGT-OS from the position of peak electric field to the N + substrate due to the reshape effect of the high-k pillar.…”
Section: Structure and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the counterpart of CSGT-MOS is located at the bottom trench. The peak electric field in the middle of the drift region is helpful to redistribute the electric field [12][13][14][15], and thus a more uniform electric field is formed in the HKP SGT-MOS and SSGT-MOS. It is clear that the electric field of HKP SGT-MOS decreases much more slowly than that of the SSGT-OS from the position of peak electric field to the N + substrate due to the reshape effect of the high-k pillar.…”
Section: Structure and Mechanismsmentioning
confidence: 99%
“…A self-biased SGT structure is proposed to further reduce its conduction losses [10,11], but the drawback is that its structure is complex and it costs additional chip area to generate the self-biased voltage. In addition, it has been reported that an SGT MOSFET with different epitaxial layers can significantly reduce the on-state resistance but requires a more complicated epitaxial process [12]. In contrast, the double split-gate structure exhibits a large BV by introducing an electric field peak in the middle of the drift region [13], in which the upper split gate is grounded, whereas the bottom split gate is kept floating.…”
Section: Introductionmentioning
confidence: 99%
“…N on‐uniform d rift r egion (NDR) doping profiles have been widely adopted in SG‐MOSFETs to improve the trade‐off relationship between BV and specific ON‐resistance ( R ON,sp ) [7]. The doping gradient is an essential consideration for the NDR profile [8].…”
Section: Introductionmentioning
confidence: 99%